Correlation Between Human Factors and the Prevention of Disasters - Barry, David L (IOS Press, 2014)
The ARW “Correlation between Human Factors and the Prevention of Catastrophes” was convened on 12-15 September, 2011 in Dnipropetrovsk, Ukraine. Ukraine has a great number of hazardous sites including nuclear plants, mining and manufacturing facilities with technically inappropriate security systems, transport routes and pipelines that are strongly subject to human influence. Severe floods in 2007 and 2008 on the Dniester and Prut rivers, affecting wide areas both in Ukraine and neighbouring countries, have demonstrated the necessity of revising security policies in the Eastern European states.